Contextualization of Class Material to Promote Meaningful Learning (2023)
ABSTRACT : This action-research aimed to identify and reflect on how the contextualization of class materials promotes meaningful learning. It was carried out in a public school in La Unión, Antioquia with 41 seventh grade students. The action strategies were the adaptation of the study material “Way to Go” textbook with information about La Unión and tasks related to the personal context of each student. The data collection instruments included the teacher’s journal, student artifacts, and a focus group with five case-participating. The findings refer to the connection that the participants achieve with the class content when the material is contextualized, the students’ attitude to develop the proposed activities, and the improvement of the students’ English level as an impact of the contextualization.